A Postmenopausal Woman with Giant Ovarian Serous Cyst Adenoma: A Case Report with Brief Literature Review - Nishat Fatema; Muna Mubarak Al Badi (Hindawi Limited, 2018)
Giant (>10 cm) ovarian cyst is a rare finding. In the literature, a few cases of giant ovarian cysts have been mentioned sporadically, especially in elderly patients. We report a 57-year-old postmenopausal woman with a giant left ovarian cyst measuring 43 × 15 × 9 cm. She was referred to us from the local health center in view of palpable pelvic mass for six-month period. Considering the age and menopausal state, we performed a total abdominal hysterectomy and bilateral salpingo-oophorectomy with excision of the giant left ovarian cyst intact and successfully without any significant complication. On histopathological examination, the cyst was confirmed as benign serous cystadenoma of the ovary. During the management of these high-risk cases of multidisciplinary approach, intraoperative and postoperative strict vigilance is necessary to avoid unwanted complications.